2016
DOI: 10.17796/1053-4628-40.3.211
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D Receptor Polymorphisms on Dental Caries

Abstract: In the future, VDR gene polymorphisms may be used as a marker for the identification of patients with high caries risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 19 publications
5
44
4
1
Order By: Relevance
“…In summary, although the results of 2 previous studies indicated that Taq I variants of the VDR gene might be associated with dental caries [Hu et al, 2015;Cogulu et al, 2016], the findings of this study suggest that this polymorphism is likely to contribute to gingival status in the Czech population. Nevertheless, further investigations are needed to confirm this finding in larger populations with different ethnic backgrounds.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…In summary, although the results of 2 previous studies indicated that Taq I variants of the VDR gene might be associated with dental caries [Hu et al, 2015;Cogulu et al, 2016], the findings of this study suggest that this polymorphism is likely to contribute to gingival status in the Czech population. Nevertheless, further investigations are needed to confirm this finding in larger populations with different ethnic backgrounds.…”
Section: Discussioncontrasting
confidence: 77%
“…In contrast to European (Czech) subjects, where the frequency of ''T'' versus ''t'' alleles was 61 versus 39% in healthy children, in the Chinese population the ''T'' allele was the dominant allele, with a frequency of 95.7%, and no ''tt'' homozygotes were observed in a group of 483 adult people [Hu et al, 2015]. In a small group of 38 caries-free children aged 6-12 years from Turkey, the frequency of ''T'' versus ''t'' alleles was 58 versus 42%, and the authors associated only the ''tt'' genotype with high caries risk [Cogulu et al, 2016]. In contrast to our study, their children had mixed (not only permanent) dentition; there are some findings that genes affecting susceptibility to caries can differ between the 2 types of teeth [Wang et al, 2010;Borilova Linhartova et al, 2016].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations